LEGAL PROTECTION OF INTERCEPTION OF COMMUNICATIONS FOR THE SPECIAL MISSIONS BASED ON THE 1969 NEW YORK CONVENTION ON SPECIAL MISSIONS (CASE STUDY ON INTERCEPTION OF COMMUNICATIONS AGAINST TURKEY SPECIAL MISSION IN 2009 LONDON G-20 CONFERENCE) - Adhika Pradya Amarendra Tardan (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2014)
AbstractInterception of Communications is an act of retrieving information from the otherparty in a manner not in accordance with applicable law. Interception ofCommunications is not regulated specifically in international law, but if therehappened to be interception of communications against diplomats, diplomaticlaws may be the basis of giving diplomatic protection. When the G-20 Summit isheld in London in 2009, British have done interception of communications againstTurkish Financial Minister and his delegates. Interception of communications is ashape of internationally wrongful act, so the problem that emerge, how is thelegal protection for Turkish Financial Minister and his delegates, based on 1969New York Convention on Special Missions.Key Word: Interception of Communications, diplomatic law.